Erste Nachweise von Pseudobranchialtumoren des Kabeljau (Gadus morhua) in der Deutschen Bucht - Watermann, B.; Dethlefsen, Volkert (1980)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010